Recent Advances in Neurosurgery - Paudel, Subodh Sharma; Luitel, Ritesh (Medical Journal of Shree Birendra Hospital, 2019)
Neurosurgery, a new subspecialty, is constantly evolving and changing over a period of time. In recent times, new insights and requirements in terms of knowledge and practice, sub-specialisation among consultants and use of multidisciplinary teams of neurosurgeons, radiologists, anaesthesiologists, and pathologists are involved to tackle neurological problems. In recent years, newer advanced technologies have expanded and redefined the discipline of neurosurgery